Clinical outcome comparison of polymethylmethacrylate bone cement with and without mineralized collagen modification for osteoporotic vertebral compression fractures - Wang, Xi (Medicine (Baltimore), 2018)
A retrospective study of consecutive patients. The purpose of this study was to compare the clinical effect of biomimetic mineralized collagen (MC) modified polymethylmethacrylate (PMMA) bone cement and traditional PMMA bone cement for the treatment of osteoporotic vertebral compression fractures (OVCF). New fracture on adjacent level is the major postoperative complication of percutaneous vertebroplasty (PVP). The clinical incidence was 12.4% to 27.7%. The increased stiffness of the treated vertebral body caused by filling bone cement is considered as one of the main reasons. A total of 30 patients treated with traditional PMMA bone cement from June 2013 to March 2016 were selected as the traditional group, while 50 patients treated with MC modified PMMA bone cement from July 2014 to March 2016 were selected as the modified group. The 2 groups were compared by injection time of the bone cements, postoperative pain relief effects, vertebral height restoration, CT value changes of the treated vertebral bodies, and postoperative complications in the clinical observations. The surgeries were successfully completed in both groups. In the treatment of OVCF, the MC modified bone cement was able to achieve the same pain relief and vertebral height restoration effects compared to traditional bone cement during the follow-ups, although the injection time of the cement was prolonged in the operation. MC modified bone cement significantly reduced the incidence of postoperative adjacent vertebral fracture from 13.3% to 2%, and significantly increased bone density of the treated vertebral bodies. The MC modified PMMA bone cement showed good clinical outcomes and better mechanical properties than the traditional bone cements.